Macroscopic comparative aspects among two species of birds of prey: Falco tunninculus (Common kestrel) and Tyto alba (Barn owl) - Alexandra Iulia Preja; Mircea Florin Cipou; Alexandru Stermin; Aurel Damian (Cluj Veterinary Journal, 2023)
Birds of prey are at the top of the food chain and play an essential role in controlling populations of birds and rodents that are harmful to habitat. This study was conducted on 11 bird carcasses, 5 Falco tunniculus carcasses and 6 Tyto alba carcasses, donated by the UBB Zoological Museum of Academic Cultural Heritage, in order to examine the gross anatomical structures of the digestive system and to highlight the anatomical differences in both carnivorous species. Dissections were conducted at the Department of Comparative Anatomy at the Faculty of Veterinary Medicine in Cluj-Napoca, according to an established protocol. The beak is short and slightly curved in both species studied, the tomial tooth being highlighted in Falco tunniculus. Conical papillae and salivary duct openings are more numerous in both species. The oropharyngeal cavity has lateral longitudinal folds of the tongue and glottis, with a distensible esophagus along its whole length in Tyto alba. Falco tunniculus, however, has ingluvium and a less distensible oesophagus. The stomach is undeveloped in both species, with the appearance of an elongated pear, and the small intestine varies in length, shorter in Falco tunniculus than in Tyto alba, but in both species it is arranged in several loops with the help of the mesenterium. The cecum is different, poorly developed, vestigial type in Falco tunniculus, and well developed, with two elongated caecal protrusions in Tyto alba. The digestive system is characteristic of carnivorous species and is a reflection of how it has adapted to feeding behavior.